2007
DOI: 10.1016/j.immuni.2007.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Initial Events in Establishing Vaginal Entry and Infection by Human Immunodeficiency Virus Type-1

Abstract: SummaryUnderstanding the initial events in the establishment of vaginal human immunodeficiency virus type-1 (HIV-1) entry and infection has been hampered by the lack of appropriate experimental models. Here, we show in an ex vivo human organ culture system that upon contact in situ, HIV-1 rapidly penetrated both intraepithelial vaginal Langerhans and CD4+ T cells. HIV-1 entered CD4+ T cells almost exclusively by CD4 and CCR5 receptor-mediated direct fusion, without requiring passage from Langerhans cells, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

21
437
1
9

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 430 publications
(468 citation statements)
references
References 34 publications
21
437
1
9
Order By: Relevance
“…Infection of biopsies of human cervical and skin of primate foreskin tissue explants show that LC can be infected [23,24]. Topical infection of human vaginal epithelial explants with HIV strongly suggested that LC and non-activated T-lymphocytes are the major cell types expressing HIV antigen in and emigrating from the explants and that they are often associated during emigration with HIV antigen concentrated at their contact region [21]. The latter suggests that LC are transferring HIV to CD4 lymphocytes.…”
Section: Lc Interactions With Important Human Viruses Hiv and Lcmentioning
confidence: 99%
See 1 more Smart Citation
“…Infection of biopsies of human cervical and skin of primate foreskin tissue explants show that LC can be infected [23,24]. Topical infection of human vaginal epithelial explants with HIV strongly suggested that LC and non-activated T-lymphocytes are the major cell types expressing HIV antigen in and emigrating from the explants and that they are often associated during emigration with HIV antigen concentrated at their contact region [21]. The latter suggests that LC are transferring HIV to CD4 lymphocytes.…”
Section: Lc Interactions With Important Human Viruses Hiv and Lcmentioning
confidence: 99%
“…A role for LC has been long advocated as they are the major HIV infectable constitutive cell type in the anogenital stratified squamous epithelium. Several in vivo and ex vivo data support a role for LC infection in HIV-1 transmission [21,22]. Vaginal simian immunodeficiency virus (SIV) infection of Rhesus macaques resulted in infected LC beneath the vaginal epithelium within the first day of infection [22].…”
mentioning
confidence: 99%
“…The CD4 molecules are expressed on epithelial and submucosal cells in both the upper and lower genital tracts of healthy women (5)(6)(7), and these cells include T lymphocytes, macrophages, dendritic cells (DCs), and Langerhans cells (8)(9)(10). The cells are all heterogeneous with regard to HIV susceptibility, which is critically dependent on the presence of the major HIV coreceptor CCR5 (7,(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…The cells are all heterogeneous with regard to HIV susceptibility, which is critically dependent on the presence of the major HIV coreceptor CCR5 (7,(11)(12)(13)(14). Also, other classes of HIV-binding molecules, including the C-type lectin receptors (CLRs), have implications for HIV susceptibility and are present on mucosal macrophages and subpopulations of DCs.…”
mentioning
confidence: 99%
“…Langerhans cells (LCs) are a subset of DCs that are, in humans, characterized by expression of CD1a, the C-type lectin Langerin and the presence of Birbeck granules [6]. LCs reside in the epidermis and stratified epithelial tissues [7][8][9]. Recently, we have shown that LCs form a barrier against HIV-1; LCs capture HIV-1 through Langerin, resulting in internalization of HIV-1 into Birbeck granules and preventing subsequent HIV-1 transmission [10].…”
mentioning
confidence: 99%